Evapotranspiration-Based Irrigation for Agriculture: Sources of Evapotranspiration Data for Irrigation Scheduling in Florida - Isaya Kisekka; Kati W. Migliaccio; Michael D. Dukes; Bruce Schaffer; Jonathan Crane; Kelly Morgan; Haimanote K. Bayabil; Sandra Guzman (EDIS)
This article is part of a series on ET-based irrigation scheduling for agriculture. The rest of the series can be found at http://edis.ifas.ufl.edu/topic_series_ET-based_irrigation_scheduling_for_agriculture.